The role of emotional styles in information avoidance regarding negative news - Mahsa Torabi; Hiwa Khezri; Samaneh Torabi (Information Research: An International Electronic Journal)
Introduction. This study explores the influence of emotional styles on students’ information avoidance behaviour, particularly about negative news.